Modelagem numérica do comportamento de ligações com parafusos auto-atarraxantes em X em corpos de prova de MLC com madeiras do tipo Eucalipto urograndis - Calil Neto, Carlito; Molina, Julio Cesar [UNESP]; Calil Junior, Carlito; Lahar, Francisco Antonio Rocco (FapUNIFESP (SciELO), 2017)
In this work was evaluated by numerical simulation, from the use of ANSYS software, version 10.0, the be-havior of steel connections made by self-tapping screws with diameter of and 11 mm, in X position, in specimens made with reforested wood of the type Eucalyptus urograndis. The stiffness k (force versus displacement) of the connection system was evaluated, in this case, by direct shear testing simulation (direct shear), considering ½ structure with applied load until the rupture of the specimen. The strategy of using ½ symmetrical structure of specimen aimed to reduce the time of numeric processing of the specimen. In the modeling of wood and steel connectors was used the finite element solid45. The numerical analysis results were com-pared with results obtained from experimental tests on wood specimens with same configuration and loadings used in experimental analysis. The calibration of the numerical model was made from the comparison of numerical and experimental curves “applied force” versus “obtained displacement”. The numerical results for the strength and stiffness k of the connection system analyzed X showed a good agreement with the experimental results and the values of experimental results were fairly smaller than the numerical values. As a result presents mainly the entire numerical modeling strategy used in this case.
Numerical modeling of connections behavior with self-tapping screws disposed in X position in specimens of MLC with eucalyptus urograndis woods
Keywords: Numeric analysis-experimental; Reforestation wood; Self-tapping screws; Shear connections